2007
DOI: 10.1002/ana.21149
|View full text |Cite
|
Sign up to set email alerts
|

DBH −1021C→T does not modify risk or age at onset in Parkinson's disease

Abstract: DBH is a candidate gene in Parkinson's disease (PD) and contains a putative functional polymorphism (-1021C→T) that has been reported to modify PD susceptibility. We examined −1021C→T in a sample of 1,244 PD patients and 1,186 unrelated control subjects. There was no significant difference in allele (p = 0.14) or genotype (p = 0.26) frequencies between the two groups. A similar result was obtained after pooling our data with those previously published. Furthermore, we found no evidence for an effect of genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
7
2
Order By: Relevance
“…Two large association studies have examined the role of this functional SNP ( DBH -1021C>T; rs1611115) with PD susceptibility [8,9]. Healy et al (2004) reported a significant increase of the TT genotype in controls, thus protective against PD in a UK Caucasian population [9].…”
Section: Introductionmentioning
confidence: 99%
“…Two large association studies have examined the role of this functional SNP ( DBH -1021C>T; rs1611115) with PD susceptibility [8,9]. Healy et al (2004) reported a significant increase of the TT genotype in controls, thus protective against PD in a UK Caucasian population [9].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were published from 1996 to 2016. Among them, 25 studies involved Caucasian populations (AD: n = 5 [20][21][22], PD: n = 3 [28][29][30], SCZ: n = 17 [34-37, 44-46, 48]), and 16 studies involved Asian populations (AD: n = 2 [23,24], PD: n = 4 [31][32][33], SCZ: n = 10 [38-43, 47, 49]). Additionally, two diagnostic criteria were used among the AD studies included (DSM-IV [56] and NINCDS-ADRDA [57]), two criteria were used for PD studies (UK PD Society Brain Bank Clinical Diagnostic Criteria (UK-PDSBB) [58] and Standard for Second National conference on Cone Diseases), and three criteria were used for SCZ studies (DSM-IV [56], DSM-III-R [56] and ICD-10 [59]).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A meta-analysis of the association between DBH polymorphisms and PD risk included seven [28][29][30][31][32][33] studies involving a total of 3482 cases and 4086 controls, including four for rs1611115 [28][29][30][31], two for rs2519152 [32,33], and one for rs732833 [31]. The analysis results showed that no associations between a collection of all three DBH polymorphisms with susceptibility to PD was observed in three genetic patterns (allelic model: P = 0.899, dominant model: P = 0.994, and recessive model: P = 0.767, shown in Fig.…”
Section: Association Between Dbh and Pdmentioning
confidence: 99%
See 2 more Smart Citations